2009
DOI: 10.1038/jhg.2009.44
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characterization of 16q-linked autosomal dominant spinocerebellar ataxia in South Kyushu, Japan

Abstract: 16q-ADCA (OMIM no. 117210) is an autosomal dominant spinocerebellar ataxia (AD-SCA) characterized by late-onset pure cerebellar ataxia and À16C4T substitution of the puratrophin-1 gene. Recently, a series of single-nucleotide polymorphisms (haplotype block) were found to be specific to 16q-ADCA. We screened patients with ataxia and found 62 patients, including four homozygotes who carry the C-T substitution of the puratrophin-1 gene. By further analysis of the patients with the haplotype block, we observed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
2
9
0
Order By: Relevance
“…Furthermore, in the present study, mild axonal sensorimotor neuropathy was identified by electromyogram. This finding is somewhat distinct from most prior reports of the disease [7][8][9]20]. Similar to our observation, Furiya et al [24] reported two cases of SCA31 accompanied by mild axonal neuropathy and orthostatic hypotension in Japan.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, in the present study, mild axonal sensorimotor neuropathy was identified by electromyogram. This finding is somewhat distinct from most prior reports of the disease [7][8][9]20]. Similar to our observation, Furiya et al [24] reported two cases of SCA31 accompanied by mild axonal neuropathy and orthostatic hypotension in Japan.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, we found one sporadic Chinese patient with SCA31 whose clinical characteristics were similar to those found in the patients in earlier studies of SCA31 in Japan [7][8][9]20].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In fact, in some areas such as South Kyushu and Nagano Prefecture, it has been found to be the most frequent ADCA subtype (27,28), making it noteworthy that SCA31 is rare (2.6% of cases) in Aomori Prefecture.…”
Section: Discussionmentioning
confidence: 99%